2021
DOI: 10.3390/molecules26195976
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers as Non-Viral Vectors in Gene-Directed Enzyme Prodrug Therapy

Abstract: Gene-directed enzyme prodrug therapy (GDEPT) has been intensively studied as a promising new strategy of prodrug delivery, with its main advantages being represented by an enhanced efficacy and a reduced off-target toxicity of the active drug. In recent years, numerous therapeutic systems based on GDEPT strategy have entered clinical trials. In order to deliver the desired gene at a specific site of action, this therapeutic approach uses vectors divided in two major categories, viral vectors and non-viral vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 231 publications
(288 reference statements)
0
2
0
Order By: Relevance
“…Dendrimers can be used as delivery vectors for genetic material ( Figure 4 ). They can transfer DNA or RNA molecules for cancer treatment [ 195 , 196 ]. PAMAM dendrimers with amino end groups can interact with the phosphate groups in nucleic acid molecules, forming complexes that will be directed to tumors and allow the transfer of genetic material through endocytosis into cancer cells and then into their nuclei [ 51 , 56 , 101 , 197 , 198 , 199 ].…”
Section: Gene Transfectionmentioning
confidence: 99%
“…Dendrimers can be used as delivery vectors for genetic material ( Figure 4 ). They can transfer DNA or RNA molecules for cancer treatment [ 195 , 196 ]. PAMAM dendrimers with amino end groups can interact with the phosphate groups in nucleic acid molecules, forming complexes that will be directed to tumors and allow the transfer of genetic material through endocytosis into cancer cells and then into their nuclei [ 51 , 56 , 101 , 197 , 198 , 199 ].…”
Section: Gene Transfectionmentioning
confidence: 99%
“…T-DM1 has low payload membrane permeability and is bound by a thioether non-cleavable linker, while T-DXd has high payload membrane permeability and is bound by a cleavable tetrapeptide-based linker. Between the two, only T-DXd presents the bystander effect [24] that leads to cell death of the neighboring tumor cells by amplifying the activity of the cytotoxic drug [25] (Figure 2b). Regarding their efficiency, a study performed by Cortes et al showed that the risk of disease progression or death was reduced in patients treated with T-DXd compared to T-DM1 [29].…”
Section: Introductionmentioning
confidence: 99%